3D printed photoacoustic shockwave transducer for cavitation research - Chan, Weiwei (2018)
In this thesis we investigate a flexible ultrasound emitter whose working principle is based on photoacoustics and is manufactured with a 3D printer. The laser generated photoacoustic waves is focused thereby achieving several hundred bars of positive pressure in water. Previous designs employed concave glass substrates decorated with catalytically grown carbon nanotubes. Here, we show that arbitrarily shaped surfaces made of polymers and printed with 3D printers allow the generation of waveforms with complex temporal and spatial shape. For optimization of the acoustic performance several materials are tested. Detailed high-frequency pressure measurements are supported with shadowgraphy images and simulations of the wave. Applications of the new transducer are shown in sample experiments demonstrating shockwave--bubble interactions, interfacial cavitation and jets from a concave gas-water interface.